2009
DOI: 10.1111/j.1477-9552.2009.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Price Elasticities of Food Trade Functions: How Relevant is the CES‐based Gravity Approach?

Abstract: The main objective of this article is to examine econometric estimates of price elasticities of food trade functions. We investigate the relevance of the prominent gravity approach. This approach is based on the assumptions of symmetric, monotone, homothetic, Constant Elasticity of Substitution (CES) preferences. We test all these assumptions using intra-European trade in cheese. In general, the assumptions made on preferences by the gravity approach are not supported by our dataset. The bias induced in the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
1
5
0
3
Order By: Relevance
“…Another related paper in the literature is by Gohin and Féménia (2009) who develop a demand equation based on Deaton and Muellbauer's (1980) almost ideal demand system and estimate it with data on intra-European Union trade in cheese products. They also find evidence against the restrictive assumptions underlying the CES-based gravity approach and stress the role of variable price elasticities.…”
Section: Introductionmentioning
confidence: 99%
“…Another related paper in the literature is by Gohin and Féménia (2009) who develop a demand equation based on Deaton and Muellbauer's (1980) almost ideal demand system and estimate it with data on intra-European Union trade in cheese products. They also find evidence against the restrictive assumptions underlying the CES-based gravity approach and stress the role of variable price elasticities.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these elasticities, normally taken from Broda et al (2006), are only available for each country at the 3-digit level of the Harmonized System classification and, thus, produce a less appropriate pattern of substitution than in Khandelwal (2010). Moreover, several authors have shown empirically the limits of the use of a Constant Elasticity of Substitution (CES) utility function when analyzing trade in food products (see Gohin and Féménia, 2009;Liu and Yue, 2012). For a deeper discussion about the limits of the CES approach in the context of new trade theory, see Neary (2009); by contrast, for a more optimistic view, see Bertoletti and Epifani (2014).…”
Section: The Khandelwal (2010) Methodsmentioning
confidence: 99%
“…Adicionalmente, la mayor parte de la literatura empírica asume que la demanda de importaciones de un bien puede separarse de la demanda correspondiente a la producción doméstica de dicho bien (e.g. Ben Kaabia & Gil, 2007;Ramirez & Wolf, 2008;Gohin & Féménia, 2009;Asche & Zang, 2013, entre otros).…”
Section: Modelo Teóricounclassified
“…En este sentido, para filtrar tal efecto es conveniente analizar la demanda por partidas específicas (e.g. Gohin & Féménia, 2009); sin embargo, en este caso resulta más complicado armar un panel balanceado con una muestra considerable para trabajar empíricamente. Por el contrario, para la lpe los precios son más uniformes, encontrándose algunos precios medios superiores que pueden explicarse por el mayor costo de envío como es en el Sudeste Asiático y en Argelia en comparación con los destinos sudamericanos.…”
Section: Metodologíaunclassified
See 1 more Smart Citation